PENGARUH UPAH, BEBAN KERJA DAN MOTIVASI KERJA TERHADAP STRES KERJA KARYAWAN PENJUALAN - Wulandari, Eka; Farida, Umi; Pristi, Eka Destriyanto (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The condition of employees who feel under pressure for the work being done is called work stress. Companies need to pay attention to several factors in order to keep employees from experiencing stress at work. The goal of this research is to know the role of independent variables in the form of wages, workload and work motivation on employee work stress by taking the research object at the research company Cahaya Ugul Nusantara Ponorogo. This research uses the principles of quantitative research. The data used in the process of extracting research data are primary data and secondary data. The parties selected as the population are employees of the sales department of PT. Cahaya Unggul Nusantara Ponorogo with a sample of 45 people. The summary of the research results is that the wage variable has a negative effect on the work stress variable, workload on the other hand has a positive effect on work stress, work motivation partially influences work stress, simultaneously all variables affect work stress